FIGURING BIDAI CRAFTSWOMEN’S FUTURE IN THE UPCOMING ASEAN ECONOMIC COMMUNITY (AEC): CASE STUDY IN THE BORDERLAND OF JAGOIBABANG - Syarifah Ema Rahmaniah; Pabali Musa; Annisa Rizqa Alamri; Ira Patriani; Elyta Elyta; Muhammad Adam Abd Azis (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Poverty on the country became a classic phenomenon that has not been resolved properly. The poverty of woman in the country veranda district Jagoibabang Bengkayang. Plantation in women and the double burden of women, the issue of trafficking in women and the exploitation of women can not be separated from women’s lives on the porch country. this research uses qualitative method, using indepth interview and data collecting technique to some splint artisans in Jagoi Village. This research describes the socio-economics dynamic of artisans in Jagoi Babang spilnt as mean to preserve the local culture that exists. There are two interesting things from this splint handicraft. First, this craft is does by ethnic Dayak and Malay. Second, most of these artisans are women. That is, solints have the opportunity as a medium of bonding relations between etnics group and at the same time as an effort to strengthen the capacity of women to preserve local wisdom and improve their family welfare. Interestingly, more dayak and Malay woman are move from spar production sector than men who are more involved in the trade sector of splint at regional, national to foreign levels. Third, this study also to explain the prepared, provlems and challenges of women handicraftsmen in facing the MEA. Therefore, this research is a descriptive framework to contribute the policy of business incubator program for female artisans toget gender equity to be strived in improving family welfare marked by increasing knowledge and awareness of the importance of business incubator in face of MEA.